TIME ANALYSIS OF HARD AND SOFT BOLUS PROCESSING - Himmlova, Lucie; Goldmann, Tomas; Ihde, Stefan; Konvickova, Svatava (Biomedical papers, 2007)
Objective: Clinical observations and mathematical models show that dental implants are influenced by the magnitude of loading. Therefore, the knowledge of mandible movement during mastication is important to assess occlusal and masticatory force vectors. The purpose of this study was to detect the path of movement of the lower jaw and to distinguish stages of mastication, duration of bolus processing and peak amplitude of mastication.Method: Motion analysis was used to record three-dimensional mandible movements. Individualized sensors were rigidly attached to the mandible of 51 study participants. At the beginning of the measurement, all subjects were asked to move the mandible in extreme positions (maximal opening and maximal lateral movements). Then, each subject masticated a bite of hard and soft food. Duration of bolus mastication and peak amplitude of mastication movement in mesio-distal, cranio-caudal and vestibulo-oral axes related to peak amplitude of marginal movements were evaluated for each subject. The chewing record of each subject was divided into three phases (chopping, grinding and swallowing), and the duration of mastication and number of closing movements were evaluated.Results: The findings of this pilot study suggest that masticatory movements vary in individuals. Bolus character influences the process duration, but not the frequency of closing movements. Neither gender nor age had any influence on either the time or frequency of bolus processing.Conclusion: Relationships to directions and magnitudes of acting chewing force should be more precisely examined since transversally acted forces during grinding are important factors in tooth/implant overloading.
Keywords: Mastication/Kinematics/3D Motion Analysis/Bolus processing/Experiment in vivo